2014
DOI: 10.1093/mnras/stu1676
|View full text |Cite
|
Sign up to set email alerts
|

The impact of reionization on the formation of supermassive black hole seeds

Abstract: Direct collapse black holes (DCBHs) formed from the collapse of atomically-cooled primordial gas in the early Universe are strong candidates for the seeds of supermassive BHs. DCBHs are thought to form in atomic cooling haloes in the presence of a strong molecule-dissociating, Lyman-Werner (LW) radiation field. Given that star forming galaxies are likely to be the source of the LW radiation in this scenario, ionizing radiation from these galaxies may accompany the LW radiation. We present cosmological simulati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 101 publications
1
46
0
Order By: Relevance
“…Here M cloud = 10 6 M ⊙ is the typical mass of the central gas cloud collapsing in an atomic cooling halo (e.g. Wise et al 2008;Johnson et al 2011Johnson et al , 2014Latif et al 2013;Choi et al 2013). Assuming a uniform cloud density, which is appropriate for our simplified one-zone calculations, this implies a cloud radius of r cloud = 30 pc (n/10 2 cm −3 ) −1/3 where n is the number density of hydrogen nuclei.…”
Section: Feedback From Lyman α Cooling Radiationmentioning
confidence: 99%
“…Here M cloud = 10 6 M ⊙ is the typical mass of the central gas cloud collapsing in an atomic cooling halo (e.g. Wise et al 2008;Johnson et al 2011Johnson et al , 2014Latif et al 2013;Choi et al 2013). Assuming a uniform cloud density, which is appropriate for our simplified one-zone calculations, this implies a cloud radius of r cloud = 30 pc (n/10 2 cm −3 ) −1/3 where n is the number density of hydrogen nuclei.…”
Section: Feedback From Lyman α Cooling Radiationmentioning
confidence: 99%
“…To form a massive POPIII star cluster thus requires a massive primordial gas cloud that can fragment and form POPIII stars in one go. One way to achieve this is by photo-ionization heating (Johnson et al 2014;Visbal et al 2016). The mean UV background (UVB) is not sufficiently high enough to ionize haloes at z > 7 (Faucher-Giguère et al 2009).…”
Section: Modelmentioning
confidence: 99%
“…In addition, the gas in this halo must remain atomic (with a temperature on the order of 10 4 K), because the formation of molecular hydrogen will enable further cooling (and thus fragmentation). To prevent the formation of H 2 , it is suggested that the halo may be irradiated by a nearby burst of star formation, producing UV light which dissociates any H 2 (Dijkstra et al 2008;Shang et al 2010;Latif et al 2013a,b;Johnson et al 2014;Regan et al 2014;Choi et al 2015;Dunn et al 2018). The resulting collapsing object may first form a "quasi-star" (Begelman et al 2006), or possibly collapse directly into a black hole (Lodato & Natarajan 2006).…”
Section: Introductionmentioning
confidence: 99%